Adipocyte associated glucocorticoid signaling regulates normal fibroblast function which is lost in inflammatory arthritis - Heather J. Faust; Tan-Yun Cheng; Ilya Korsunsky; Gerald F. M. Watts; Shani T. Gal-Oz; William V. Trim; Suppawat Kongthong; Anna Helena Jonsson; Daimon P. Simmons; Fan Zhang; Robert Padera; Susan Chubinskaya; et al. (Nature Communications, 2024)
Abstract Fibroblasts play critical roles in tissue homeostasis, but in pathologic states they can drive fibrosis, inflammation, and tissue destruction. Little is known about what regulates the homeostatic functions of fibroblasts. Here, we perform RNA sequencing and identify a gene expression program in healthy synovial fibroblasts characterized by enhanced fatty acid metabolism and lipid transport. We identify cortisol as the key driver of the healthy fibroblast phenotype and that depletion of adipocytes, which express high levels of Hsd11b1, results in loss of the healthy fibroblast phenotype in mouse synovium. Additionally, fibroblast-specific glucocorticoid receptor Nr3c1 deletion in vivo leads to worsened arthritis. Cortisol signaling in fibroblasts mitigates matrix remodeling induced by TNF and TGF-β1 in vitro, while stimulation with these cytokines represses cortisol signaling and adipogenesis. Together, these findings demonstrate the importance of adipocytes and cortisol signaling in driving the healthy synovial fibroblast state that is lost in disease.